Treatment of neovascular age-related macular degeneration: one year real-life results with intravitreal Brolucizumab - Settimio Rossi; Carlo Gesualdo; Ernesto Marano; Raffaele Perrotta; Maria Consiglia Trotta; Antonio Del Giudice; Francesca Simonelli (Frontiers in Medicine)
BackgroundAge-related macular degeneration (AMD) is a prevalent cause of irreversible vision loss worldwide, particularly among the elderly population. Two forms of late AMD are described: neovascular AMD (nAMD), characterized by abnormal choroidal blood vessel growth, and atrophic (dry) AMD, involving retinal cell degeneration. Intravitreal anti-vascular endothelial growth factor (anti-VEGF) agents have transformed nAMD treatment, with Brolucizumab emerging as a promising therapy. The aim of this study is to provide the real-life anatomical-functional and safety results, after 1 year of treatment experience with Brolucizumab.MethodsThis is a retrospective observational real-life study in which 44 patients (44 eyes) diagnosed with nAMD and treated with Brolucizumab were enrolled. We identified two groups: group 1 (24 treatment-naïve eyes) that received a loading dose of 3 monthly intravitreal injections of Broluciziumab 6 mg (0.05 mL solution) + Q8w/Q12w regimen, and a Group 2 (20 non-naïve eyes) which performed 1 injection + ProReNata (PRN) scheme. Monthly, all participants underwent comprehensive ophthalmological evaluation until 12 months follow-up.ResultsWe observed a significant improvement in best corrected visual acuity (39 ± 15 L vs. 30 ± 17 L; p < 0.01) and central retinal thickness (265 ± 89 μ vs. 360 ± 129 μ; p < 0.0001) at the end of follow-up without any differences between treatment-naïve and non-naïve patients. These results were obtained with a low number of injections (3.7 ± 1.9) with only one case of intraocular drug-related adverse event. Finally, the presence of subretinal hyperreflective material correlates with lower visual recovery.DiscussionOur findings highlight the efficacy of Brolucizumab in managing wet-AMD and suggest its role for long-term efficacy in stabilizing retinal exudation and fluid accumulation, resulting in improved visual prognosis.